Caregiver Stigma and Burden in Memory Disorders: An Evaluation of the Effects of Caregiver Type and Gender. (28th January 2016) - Kahn, Phoebe V.; Wishart, Heather A.; Randolph, Jennifer S.; Santulli, Robert B.
Abstract : Despite considerable gains in public awareness of dementia, dementia patients and their caregivers continue to be stigmatized. Previous work has explored stigma and burden among adult children of persons with dementia in Israel, but no similar data exist for spousal caregivers or caregivers in general in the United States. This study examines the differences in stigma and burden experienced by spousal and adult child caregivers and male and female caregivers of persons with dementia. Eighty-two caregivers were given the Zarit Burden Inventory Short Form (ZBI) and the Caregiver Section of the Family Stigma in Alzheimer's Disease Scale (FS-ADS-C). Scores on the FS-ADS-C and ZBI were positively correlated (r s = . 51, p < . 001 ). Female caregivers reported experiencing more stigma on the FS-ADS-C (t ( 80 ) = −4.37, p < . 001 ) and more burden on the ZBI (t ( 80 ) = −2.68, p = . 009 ) compared to male caregivers, and adult child caregivers reported experiencing more stigma on the FS-ADS-C (t ( 30.8 ) = −2.22, p = . 034 ) and more burden on the ZBI (t ( 80 ) = −2.65, p = . 010 ) than spousal caregivers. These results reinforce the importance of support for caregivers, particularly adult child and female caregivers who may experience higher levels of stigma and burden.